Management of Malnutrition Based on Multidisciplinary Team Decision-Making in Chinese Older Adults (3M Study): A Prospective, Multicenter, Randomized, Controlled Study Protocol - Ji, Tong; Zhang, Li; Han, Rui; Peng, Linlin; Shen, Shanshan; Liu, Xiaolei; Shi, Yanqing; Chen, Xujiao; Chen, Qiong; Li, Yun; Ma, Lina (Frontiers in Nutrition, 2022)
Background: In hospital settings, malnutrition affects 30–50% of aged inpatients and is related to a higher risk of hospital complications and death. This study aims to demonstrate the effectiveness of a tailored optimum nutritional therapy in malnourished, elderly inpatients based on multidisciplinary team recommendations in hopes of decreasing the incidence of deleterious clinical outcomes. Methods and Design: This trial will be a multicenter, open-label, randomized control trial conducted in the geriatric wards of at least five hospitals in five different regions. We aim to include 500 inpatients over the age of 60 with or at risk of malnutrition based on a Mini Nutritional Assessment Short-Form (MNA-SF) score of ≤11 points and the Global Leadership Initiative on Malnutrition with an expected length of stay of ≥7 days. Eligible inpatients will be randomized into a 1:1 ratio, with one receiving a multidisciplinary team intervention and the other receiving standard medical treatment or care alone. A structured comprehensive assessment of anthropometry, nutritional status, cognition, mood, functional performance, and quality of life will be conducted twice. These assessments will take place on the day of group allocation and 1 year after discharge, and a structured screening assessment for elderly malnutrition will be conducted at 3 months and 6 months after discharge using the MNA-SF. The primary outcome will be nutritional status based on changes in MNA-SF scores at 3 months, 6 months, and 1 year. The secondary outcome will be changes in cognition, mood, functional status, length of hospital stay, and all-cause mortality 1 year after discharge. Discussion: Guided by the concept of interdisciplinary cooperation, this study will establish a multidisciplinary nutrition support team that will develop an innovative intervention strategy that integrates nutritional screenings, evaluations, education, consultation, support, and monitoring. Moreover, nutritional intervention and dietary fortification will be provided to hospitalized elderly patients with or at risk of malnutrition. The nutrition support team will formulate a clinical map for malnutrition in elderly patients with standardized diagnosis and treatment for malnutrition in this population.